Comparison between Cefoxitin disk diffusion, Crome agar and EPI-M Screening Kit for Detection of Methicillin- Resistant Staphylococcus aureus - Alwash, Samarah; Saleh, Dhuha (Iraqi Journal of Science, 2024)
Specimens have been collected from one hundred and seventeen patients residing in local hospitals, 33 with burns and 84 wound injuries,. Three different methods ,Cefoxitin disk diffusion, EPI-M Screening Kit and Crome agar (MeReSa agar)with selective supplement were used to detect methicillin-resistant Staphylococcus aureus (MRSA) . A comparison was made between these 3 methods according to the results. It was found that the results of the Cefoxitin disk diffusion test were compatible with the results of culturing on Crome agar, while those obtained from the EPI-M Screening kit were not accurate and some of them gave false negative results.